2009
DOI: 10.1097/brs.0b013e3181aa6175
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Healthy Controls and Two Clinical Subgroups of Nonspecific Chronic Low Back Pain Patients Using Trunk Muscle Activation and Lumbosacral Kinematics of Postures and Movements

Abstract: Selected biomechanical variables were predictors for subgroup membership and were able to discriminate the 3 subgroups. This study adds further support toward the validation of the proposed classification system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 37 publications
7
138
0
2
Order By: Relevance
“…16 In another study, we investigated sag ittal plane standing postures in 14year olds and identified 4 posture subgroups (neutral, sway back, flat back, and lordot ic). 58 A number of relationships between LBP and nonneutral spinal postures were identified.…”
Section: Multidimensional Factors and Adolescent Lbp: Physical Factorsmentioning
confidence: 99%
“…16 In another study, we investigated sag ittal plane standing postures in 14year olds and identified 4 posture subgroups (neutral, sway back, flat back, and lordot ic). 58 A number of relationships between LBP and nonneutral spinal postures were identified.…”
Section: Multidimensional Factors and Adolescent Lbp: Physical Factorsmentioning
confidence: 99%
“…4,8,22 Consideration of poor ability to dissociate movements between spine regions is common in these classification methods 10,22 and other assessments for LBP. 25 Poor movement dissociation is been reported previously.…”
Section: Relevance For Identification Of Lbp Subgroupsmentioning
confidence: 99%
“…4,5,19,29 Recovery from LBP does not ensure restoration of spine function or movement, and recurrent LBP involves persistent alterations of motor control, including modified coordination between short/deep (eg, multifidus) and long/ superficial (eg, thoracic erector spinae) paraspinal muscles, with a tendency to contract these muscles en masse rather than to activate …”
mentioning
confidence: 99%
“…The laboratory tests analysed in Study IV (Dankaerts et al, 2009) involved commonly reported aggravating spinal postures and movements that form part of the basis of the clinical classification process. The results of Study IV demonstrated that a Statistical Classification Model identified five lumbo-sacral kinematics (lower lumbar spine kinematics in sitting and forward bending) and two trunk muscle activation (lack of flexion relaxation of the superficial fibres of lumbar multifidus in slump sitting and end range of forward bending) variables that were able to correctly classify 96.4% of cases and to discriminate the three groups (no-LBP, AEP and FP).…”
Section: Can Clinicians Agree On the Classification Of Nonspecific Chmentioning
confidence: 99%